PATHOPHYSIOLOGICAL AND PATHOMORPHOLOGICAL EVALUATION OF THE PHARMACOCORRECTION OF INDUCED DISLIPIDEMIA - V. G. Banzaraksheev (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The article presents the results of pathophysiological and pathomorphological evaluation of effectiveness of pharmacotherapy in experimental dyslipidemia. Dyslipidemia was induced in rats by prescribing the atherogenic diet for 12 weeks. Pharmacotherapeutic effectiveness of the complex plant remedy based on Tibetan medicine was studied. The tested remedy in the form of decoction was introduced intragastrically in the dose of 1 mL per 100 g of weight once a day during the whole period of the experiment. The control group received the distilled water according to the same scheme. It is established that atherogenic dyslipidemia was accompanied by structural changes in all membranes of aorta in the form of edema, leukocyte infiltration and desquamation of endothelial cells. Morphometric parameters of aorta were characterized by increasing thickness of t. adventitia, the total width of t. intima and t. media, as well as the total thickness of aortic wall. In the blood of animals the level of circulating endothelial cells increased by 2,17 times, platelet aggregation increased by 17,6 % on average. The prescription of phytoremedy reduced the severity of pathomorphological and morphometrical changes in aorta, decreased the content of circulating endothelial cells in blood by 38 %, inhibited platelet aggregation by 30 % on average.